Digestible energy and nutrient digestibility of full-fat soybean meal in adult and growing guinea pigs - Chillpa-Sencia, Celia; Moscoso, Juan; Chino-Velasquez, Liz; Molina-Botero, Isabel; Gómez, Oscar; Arjona-Smith, Mario (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The use of full-fat soybean meal (FSBM) in feeding guinea pigs would be a good alternative to improve dietary protein, but little is known about the use of their nutrients in this animal species. This study aimed to determine the nutrient digestibility and energy digestible of FSBM and the effects of its incorporation in guinea pigs’ diets. Thirty male guinea pigs were used, aged two (15 animals) and 10 weeks (15 animals). A basal diet was used, from which the weight/weight substitution was carried out at proportions of 15 and 30 % inclusion of FSBM. The digestibility of nutrients in the diets differed between ages, being higher in adults than in growing (p<0.001). The digestibility of DM and nutrients of FSBM was high, being higher in adult guinea pigs (76.94 % DM, 77.56 % OM, 82.34 % CP, 86.87 % EE, and 60.96 % CF) than growing (71.78 % DM, 72.35 % OM, 66.24 % CP, 60.37 % EE and 50.41 % CF) (p<0.001). The digestible energy was 3375 and 3093 kcal.kg-1 DM for adult and growing guinea pigs respectively (p<0.001). FSBM meal is a good option for feeding growing and adult guinea pigs due to its high nutritional value and digestibility.